IPTEKS PERHITUNGAN PENYUSUTAN DENGAN METODE GARIS LURUS DAN SALDO MENURUN PADA ASET TETAP - Niu, Fitria Ayu Lestari; Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2020)
Tax is a people's contribution to the state treasury based on law (which can be enforced) with no return. Tax planning is one form of tax management function in an effort to save tax legally, one of which is by choosing a method of depreciation that can support tax efficiency. The depreciation method permitted in taxation in Indonesia consists of two methods, namely the straight-line method and the declining balance method. Both of them were used in the calculation and recognition of depreciation expense have an impact on the smaller amount of net income generated resulting in a smaller tax burden borne by the taxpayer. The application of the straight-line method helps taxpayers save tax in the years the middle of the economic period while the declining balance method helps taxpayers save tax in the early years of reporting period. This means that both the straight-line method and the declining balance method have their advantages and disadvantages.